STRATEGI BADAN NARKOTIKA NASIONAL KABUPATEN KUANTAN SINGINGI DALAM MENANGGULANGI PENYALAHGUNAAN NARKOBA TAHUN 2022 - Pratiwi, Dian; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Abuse and illicit trafficking of narcotics is currently a major problem both nationally and internationally. Drug abuse has been proven to have damaged the future of the nation, damaged human character, damaged the physical and health of the community. The Kuantan Singingi Regency National Narcotics Agency (BNNK) is a professional non-ministerial government agency that operates to prevent, eradicate, abuse and illicit trafficking of narcotics, psychotropics and other addictive substances as mentioned in Republic of Indonesia Law No. 35 of 2009 about Narcotics. This research aims to determine the success of the strategies and inhibiting factors of the Kuantan Singingi Regency National Narcotics Agency in tackling drugs. This research uses the theory of strategic management from Wheelen-Hunger. This research uses a qualitative approach using descriptive research. Data collection techniques were carried out using interviews and documentation. The data analysis technique used in this research has steps such as data collection, data reduction, data presentation and drawing conclusions. The results of this research explain that the National Narcotics Agency of Kuantan Singingi Regency has been optimal in implementing drug prevention, this can be seen from several strategic management indicators including: external analysis, internal analysis, mission, organizational goals, strategies, policies, programs, budgets, procedures , as well as performance. The performance of BNNK Kuantan Singingi in 2022 has been said to be good, this can be seen from the realization of the program based on the Performance Success Index (IKK). However, in its implementation there are still various obstacles, such as the wide coverage of BNNK's work area which is not balanced with the distribution of employees and the lack of facilities and infrastructure to cover prevention activities. Keywords : Prevention, drugs, District National Narcotics Agency